Disruption of the G(1)/S Transition in Human Papillomavirus Type 16 E7-Expressing Human Cells Is Associated with Altered Regulation of Cyclin E - Martin, Larry G. (American Society for Microbiology, 1998)
The development of neoplasia frequently involves inactivation of the p53 and retinoblastoma (Rb) tumor suppressor pathways and disruption of cell cycle checkpoints that monitor the integrity of replication and cell division. The human papillomavirus type 16 (HPV-16) oncoproteins, E6 and E7, have been shown to bind p53 and Rb, respectively. To further delineate the mechanisms by which E6 and E7 affect cell cycle control, we examined various aspects of the cell cycle machinery. The low-risk HPV-6 E6 and E7 proteins did not cause any significant change in the levels of cell cycle proteins analyzed. HPV-16 E6 resulted in very low levels of p53 and p21 and globally elevated cyclin-dependent kinase (CDK) activity. In contrast, HPV-16 E7 had a profound effect on several aspects of the cell cycle machinery. A number of cyclins and CDKs were elevated, and despite the elevation of the levels of at least two CDK inhibitors, p21 and p16, CDK activity was globally increased. Most strikingly, cyclin E expression was deregulated both transcriptionally and posttranscriptionally and persisted at high levels in S and G(2)/M. Transit through G(1) was shortened by the premature activation of cyclin E-associated kinase activity. Elevation of cyclin E levels required both the CR1 and CR2 domains of E7. These data suggest that cyclin E may be a critical target of HPV-16 E7 in the disruption of G(1)/S cell cycle progression and that the ability of E7 to regulate cyclin E involves activities in addition to the release of E2F.